2006
DOI: 10.1002/rmv.502
|View full text |Cite
|
Sign up to set email alerts
|

Molecular studies of Varicella zoster virus

Abstract: VZV is a highly cell-associated member of the Herpesviridae family and one of the eight herpesviruses to infect humans. The virus is ubiquitous in most populations worldwide, primary infection with which causes varicella, more commonly known as chickenpox. Characteristic of members of the alphaherpesvirus sub-family, VZV is neurotropic and establishes latency in sensory neurones. Reactivation from latency, usually during periods of impaired cellular immunity, causes herpes zoster (shingles). Despite being one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 223 publications
1
42
0
Order By: Relevance
“…Although our isolates had no such mutations, exogenic reinfection may occur in immunocompetent and immunocompromised individuals, and recombinant virus could be released during subclinical virus replication or a shingles episode. Both serologic evidence and confirmed cases of reinfection with VZV have been described (3,13,40; see also the review of Quinlivan and Breuer [39]). Another open question is the mechanism of recombination.…”
Section: Genotyping Of Vzv Field Isolatesmentioning
confidence: 88%
“…Although our isolates had no such mutations, exogenic reinfection may occur in immunocompetent and immunocompromised individuals, and recombinant virus could be released during subclinical virus replication or a shingles episode. Both serologic evidence and confirmed cases of reinfection with VZV have been described (3,13,40; see also the review of Quinlivan and Breuer [39]). Another open question is the mechanism of recombination.…”
Section: Genotyping Of Vzv Field Isolatesmentioning
confidence: 88%
“…At least for four of the six patients, the rise of anti-VZV IgG levels was not accompanied by herpes zoster nor other clinical symptoms of VZV disease, indicating subclinical reactivation or reinfection in these cases. Evidence of subclinical reactivation of VZV was previously obtained by measuring significant rises of anti-VZV IgG levels after household exposure of seropositive individuals (reviewed in Quinlivan and Breuer) 24 ; by detection of VZV DNA, in patients with malignancies without clinical symptoms of VZV disease 38 ; and by intrathecal synthesis of anti-VZV antibodies in the absence of a history of herpes zoster, in HIV-infected individuals. 39 In a long-term longitudinal study, with a follow-up of 45 healthy subjects for up to 26 years, it was observed that there were rises of anti-VZV antibody levels by more than 2-fold, with an incidence of 1.6 events per 100 person-years.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date it is not clear that these mutations play an important role in the attenuation of vOka (1,5). In this study, ORF 62 of VZV wild-type strains was analyzed by DNA sequencing.…”
Section: Varicella-zoster Virus Strains Of European Genotypes Have Dementioning
confidence: 99%